Correlation Between Livable Housing, BCG Immunization Coverage, and Population Density with Child Tuberculosis Incidence in East Java Province 2020-2022 - Prameswari, Ambarsih; Hendrati, Lucia Yovieta (JURNAL KESEHATAN LINGKUNGAN, 2024)
Introduction: Mycobacterium tuberculosis bacteria can cause tuberculosis disease. In 2022, East Java Province reported 8,398 cases of child tuberculosis with a discovery coverage of 105.6%. This study aims to describe the distribution of child tuberculosis incidence in East Java Province by mapping and analyzing the correlation between livable houses, BCG immunization coverage, and population density with the incidence of child tuberculosis in 38 districts/cities in East Java Province from 2020 to 2022. Methods: This was a descriptive approach with a population correlation study design using the Spearman correlation statistical test. Secondary records from the East Java Health Profile 2020, 2021, and 2022 were used in this study. Thirty-eight districts/cities in the province of East Java comprised the study's population. Results and Discussion: This study showed that there has been a positive correlation between BCG immunization coverage in 2020 (r=0.043); 2021 (r=0.140); 2022 (r=0.214) and population density 2020 (r=0.082); 2021 (r=0.102); and 2022 (r=0.174) with the incidence of child tuberculosis. Meanwhile, the correlation between livable houses and the incidence of child tuberculosis is negative in 2020 (r=-0.990) and 2022 (r=-0.047) but positive in 2021 (r=0.078). Conclusion: The increase in BCG immunization coverage and population density aligns with the increase in child tuberculosis cases. Meanwhile, an increase in the percentage of access to livable houses is followed by a decrease in the incidence of child tuberculosis.